KARAKTERISTIK PENDERITA HIV/AIDS DI KLINIK VCT RUMAH SAKIT UMUM HKBP BALIGE TAHUN 2008 – 2012 - Desima M Hutapea; Prof.dr. Sori Muda Sarumpaet MPH; drh. Rasmaliah M.Kes (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2013)
ABSTRACT Acquired Immune Deficiency Syndrome (AIDS) is a collection of symptoms caused by a drop in immunity due to infection with Human Immunodeficiency Virus (HIV). HIV/AIDS is a disease of Sexually Tansmitted Infections (STIs) with increasing cases every year. The aim of the study is to determine the characteristics of the patients with HIV/AIDS utilized VCT’s clinic of HKBP Balige General Hospital in 2008 – 2012. The type of the study is descriptive study with case series design. The population is all the data of people with HIV/ADS totaling 145 data and used as sample. Univariate data were analyzed descriptively while bivariate data were analyzed using Chi-Square test with 95% CI. The results of the study indicated that the trend of patient with HIV/AIDS frequency is increasing according to the linear equation y = – 4,3 + 11,1x. The distribution of frequency based on sociodemographic, the highest population is in the age group of 30-39 years old (58,6%), male (75,2%), senior high school (66,9%), job self-employed (36,6%), married (77,2%), in the area of Toba Samosir regency (62,8%). Highest transmission is heterosexual transmission of promiscuity (66,9%), length suffered of AIDS since diagnosed <1 year (74,1%), the highest opportunistic infection type is oral candidiasis (33,8%), death (54,6%). There is a significant differentiation of proportion between sex based on the transmission infection (p=0,000), married based on the transmissions infection (p=0,000), length of life based on last condition (p=0,000). There is no significant differentiation of proportion between married based on sex (p=0,584), age based on the transmissions infection (p=0,216) and work based on the transmissions infection (p=0,810). Expected to groups at high risk of HIV/AIDS to not promiscuity in order to prevent the heterosexual transmission, VCT’s clinic of HKBP Balige General Hospital expected to introduce VCT’s services and promote early inspection, increase patient assistance program, and complete the record data of job self-employed in job variable. Key Words : HIV/AIDS, Characteristic of Patients, VCT’s Clinic of HKBP Balige General Hospital